One shot at forever : a small town, an unlikely coach, and a magical baseball season - Ballard, Chris (Hyperion, 2012)
In 1971, a small-town high school baseball team from rural Illinois playing with hand-me-down uniforms and peace signs on their hats defied convention and the odds. Led by an English teacher with no coaching experience, the Macon Ironmen emerged from a field of 370 teams to become the smallest school in Illinois history to make the state final, a distinction that still stands. There, sporting long hair, and warming up to Jesus Christ Superstar, the Ironmen would play a dramatic game against a Chicago powerhouse that would change their lives forever.